Constitutional and Legal Protection of the Right in Personal Life - Shatnawi, Fiasal; Hatamleh, Saleem; Rfoua , Amal (Dirasat: Shari’a and Law Sciences, 2020)
The right to private life is one of the fundamental constitutional rights inherent to the natural person in his human capacity as a public asset and is the backbone of personal freedom, a fundamental pillar of human rights and public freedoms, and the foundation of the structure of every healthy society. Accordingly, this right requires respect for authority and individuals, and at the same time requires that the authorities guarantee constitutional and legal protection against unlawful violation. The provisions of the Islamic Sharia have included many Sharia provisions that urge that human privacy and dignity must be respected, and the declarations of human rights are considered one of the most important elements of the historical development of the human right to privacy. Article 7 of the Jordanian constitution of 1952 and its amendments of 2011 stipulates that "any attack on public rights and freedoms or the inviolability of the private life of Jordanians is a crime punishable by law". The Jordanian legislator has combined two types of protection of the inviolability of private life; the first is civil protection, which aims to compensate the injured, and the second is Penal protection, represented by penal punishment, which aims to repair the damage. This study examines the appropriateness of the legal norms approved by the Jordanian legislator to protect against attacks on the human right to private life, whether those contained in the Constitution, the civil code, or the Criminal Code.